Identificação de falhas em uma indústria sucroalcooleira por meio de manutenção centrada em confiabilidade e análise de modos e efeitos de falha - Coelho, Rafael Scatena (Universidade Federal de São Carlos, 2025)
The sugar and ethanol industry is a sector that demands high equipment reliability and availability, essential factors to ensure continuous, efficient, and profitable production. However, this industry constantly faces challenges related to high maintenance costs and the risk of failures, which can lead to unexpected shutdowns and financial losses. Therefore, increasing asset reliability to reduce maintenance costs becomes crucial. This study applied the principles of Reliability-Centered Maintenance (RCM) to a piece of equipment in a sugar and ethanol plant. RCM is a strategic approach aimed at optimizing maintenance by considering asset reliability and managing the risks associated with failures. To achieve this, the FMEA (Failure Modes and Effects Analysis) tool was used to identify, classify, and prioritize failures. Based on this analysis, preventive and predictive maintenance plans were developed for the analyzed equipment. The goal was to improve risk and failure control by identifying root causes and increasing equipment availability. In the long term, the objective is to significantly reduce unplanned downtime during the harvest period and extend the useful life of the equipment. This work aimed to demonstrate the importance of applying these concepts to avoid subjective failure analysis. In doing so, it sought to assess the feasibility of applying this methodology to other sectors and equipment within the industry, ensuring greater reliability throughout the production process.
Failure identification in a sugar and alcohol industry by means of reliability-centered maintenance and failure modes and effects analysis
Keywords: Manutenção; Confiabilidade; Análise de modos e efeitos de falha; ENGENHARIAS::ENGENHARIA MECANICA::PROJETOS DE MAQUINAS